03 NILAI TAMBAH PEMANFAATAN LIMBAH TERNAK SAPI PENGOLAHAN PUPUK CAIR ORGANIK DI DESA TAMARAMPU KECAMATAN MANDAI KABUPATEN MAROS - Jurnal Agribis; Muh Attin Maulana; Zulkifli Zulkifli; Abd. Asis Pata (Jurnal Agribis, 2021)
Potential cattle waste in the form of solid and liquid waste that can be detrimental and simple treatment of livestock waste. This study aims to determine the value added obtained in the processing of cattle waste into liquid fertilizer through the cattle urine urine system to find out the added value of cattle waste in Tamarampu Environment Bontoa Village, Mandai District, Maros Regency. This research was conducted in January - June 2017. The determination of the research site was based on the consideration that, in the Tamarampu Environment, there were so many cattle ranchers who did not yet know how to process their livestock waste which was of very high economic value. Respondents in this study were cattle breeders in the Tamarampu Environment. Determination of respondents was carried out on a primary basis. The process of making liquid fertilizer with a liquid fertilizer procurement system and the analysis used is the calculation of value added. The results of the processing of cattle waste provide an added value of Rp. 5,200 / liter through the processing and calculation of added value.